2002
DOI: 10.1074/jbc.m200666200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wild-type or Mutant Parkin on Oxidative Damage, Nitric Oxide, Antioxidant Defenses, and the Proteasome

Abstract: Mutations in Parkin (a ubiquitin protein ligase) are involved in autosomal recessive juvenile parkinsonism, but it is not known how they cause nigral cell death. We examined the effect of Parkin overexpression on cellular levels of oxidative damage, antioxidant defenses, nitric oxide production, and proteasomal enzyme activity. Increasing expression of Parkin by gene transfection in NT-2 and SK-N-MC cells led to increased proteasomal activity, decreased levels of protein carbonyls, 3-nitrotyrosine-containing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
95
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(115 citation statements)
references
References 61 publications
17
95
1
2
Order By: Relevance
“…Of these five genes, ␣-Syn, parkin, and DJ-1 have been most intensively studied. Studies using in vivo animal models and in vitro cell culture have linked mutations of these genes to impairments of mitochondrial structure and function and oxidative stress response, reinforcing the general involvement of mitochondrial dysfunction and oxidative stress in PD pathogenesis (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Consistent with this notion, these proteins have been shown to be present in mitochondria or interact with mitochondrial proteins (8,(22)(23)(24), suggesting that they may directly regulate mitochondria function.…”
supporting
confidence: 56%
“…Of these five genes, ␣-Syn, parkin, and DJ-1 have been most intensively studied. Studies using in vivo animal models and in vitro cell culture have linked mutations of these genes to impairments of mitochondrial structure and function and oxidative stress response, reinforcing the general involvement of mitochondrial dysfunction and oxidative stress in PD pathogenesis (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Consistent with this notion, these proteins have been shown to be present in mitochondria or interact with mitochondrial proteins (8,(22)(23)(24), suggesting that they may directly regulate mitochondria function.…”
supporting
confidence: 56%
“…Our finding that altered GstS1 activity inf luences the parkin mutant phenotypes raises the possibility that parkin may also offer protection from the effects of oxidative stress. Further support for this hypothesis comes from the findings that oxidative damage in f lies, mice, and cell lines and sensitivity to oxidative stress agents in f lies and cell lines correlates inversely with parkin activity (19,(32)(33)(34). Our recent results from transcriptional profiling of parkin mutants and a genetic screen for parkin modifiers also demonstrate that oxidative stress response elements are up-regulated and that mutations in oxidative stress response components enhance the parkin mutant phenotypes (15).…”
Section: Discussionmentioning
confidence: 53%
“…It has been suggested that the presence of mutant Parkin, a multiprotein E3 ubiquitin ligase complex, which in turn is part of the ubiquitin-proteasome system which mediates the targeting of proteins for degradation, increases oxidative stress and sensitizes cells to death induced by different insults. 27 Recent publications have shown a direct link between Parkin and mitochondria. Parkin is specifically recruited to impaired mitochondria and activates the process of mitophagy.…”
Section: Discussionmentioning
confidence: 99%